Detection of Contamination Salmonella sp. of Beef in Banyuwangi Traditional Market - Hanifa, Muril Hizriyana; Tyasningsih, Wiwiek; Yunita, Maya Nurwantanti (Jurnal Medik Veteriner, 2022)
Salmonella sp. is one of the bacteria from Food-Borne Disease agents, can contaminate meat and cause salmonellosis. According to National Indonesian Standard 2009, meat is safe for consumption if it has a negative result of salmonella in 25 grams of meat. The purpose of this study was to determine whether there was contamination of Salmonella sp. on beef sold in the traditional market of Banyuwangi District. A total of 18 samples used in this study were taken according to the criteria for isolation and identification. All samples were enriched with the pre-enrichment stage using Lactose Broth media, and the enrichment medium using Tetrathionate Broth. Furthermore, in the isolation stage using Salmonella Shigella Agar (SSA) media. Then proceed with the identification stage using the Triple Sugar Iron Agar (TSIA) test, the Sulfide Indole Motility (SIM) test, and the Urease test. The results showed that 5 out of 18 samples tested positive for Salmonella.